Visitor revisit intention and perceived values towards Tunku Abdul Rahman Marine Park, Sabah - Boyd Sun Fatt; Nik Alif Amri Nik Hashim; Mohd Ariff Alias; Zaimatul Awang; Fauzan Hafiz Muhammad Safr; Shirley @ Marylinda Bakansing; Rovitha Godou; Grace Sinidol (Society of Business and management, 2021)
Tunku Abdul Rahman Marine Park (TARMP) in Sabah, Malaysia is made up of five beautiful islands worthy of attention from domestic and international tourists owing to the richness of natural resources that the visitors could not resist. As a result, the perceived hedonic and utilitarian values will eventually influence the intention of the visitors to revisit this destination in the future. Many studies have been conducted to understand visitor revisit intention in relation to hedonic and utilitarian values at shopping malls, restaurants, or hotels; however, further studies are yet to be conducted in the context of tourist destinations, especially Marine Park. Hence, this study aims to examine the perceived hedonic and utilitarian values of visitors and their revisit intention to Tunku Abdul Rahman Marine Park. A set of 146 questionnaires was distributed to the domestic tourists using a convenience sampling technique and the results showed that that the hedonic and utilitarian values are among the factors of motivation that attract the visitors to revisit TARMP. This study contributes to new perspectives of visitor revisit intention, especially in the context of tourism. This study also offers practical implications for the tourism board to plan the marketing strategies to attract more visitors to TARMP in the future.